Engagement in perinatal outpatient services among women in recovery from opioid use disorders. Issue 4 (2nd October 2021) - Peacock-Chambers, Elizabeth; Paterno, Mary T.; Kiely, Daniel; Fioroni, Tinamarie; Byatt, Nancy; Friedmann, Peter D.
Abstract: Background: Despite being highly motivated to recover, pregnant and postpartum women with opioid use disorders (OUD) are at high risk of relapse and death. While many services mitigate this risk, engagement in voluntary, outpatient services remains low. Our aim was to understand the experiences of and factors influencing outpatient service engagement during the perinatal period among women in recovery from OUD. Methods: We conducted semi-structured interviews about perinatal experiences engaging with outpatient services, with 20 women in recovery aged 22–46 years who had children between 6 months and 10 years old. Interviews were audio-recorded, transcribed, coded, and analyzed using conventional content analysis. Results: Women described a continuum of 'collaborative engagement' experiences, defined by the extent to which they perceived their providers or service organizations were invested in their journeys as a partners and advocates. The ability to achieve collaborative engagement depended upon two factors: (1) the woman's transformational development as a mother and woman in recovery, and (2) her perception of the providers' ability to meet her multifaceted needs. Conclusions: Women in recovery from OUD may experience deeper engagement in voluntary outpatient perinatal services when they perceive that their providers are invested and collaboratively engaging in their recovery and personal growth. Future research should test whether collaborative engagement improves service retention. Abbreviations: IPV: Intimate Partner Violence; OUD: opioid use disorder